Engineered Tumor-Targeted T Cells Mediate Enhanced Anti-Tumor Efficacy Both Directly and through Activation of the Endogenous Immune System - Avanzi, Mauro P.; Yeku, Oladapo; Li, Xinghuo; Wijewarnasuriya, Dinali P.; van Leeuwen, Dayenne G.; Cheung, Kenneth; Park, Hyebin; Purdon, Terence J.; Daniyan, Anthony F.; Spitzer, Matthew H.; Brentjens, Renier J. (Cell reports (Cambridge), 2018)
Chimeric antigen receptor (CAR) T cell therapy has proven clinically beneficial against B cell acute lymphoblastic leukemia and non-Hodgkin’s lymphoma. However, suboptimal clinical outcomes have been associated with decreased expansion and persistence of adoptively transferred CAR T cells, antigen-negative relapses, and impairment by an immunosuppressive tumor microenvironment. Improvements in CAR T cell design are required to enhance clinical efficacy, as well as broaden the applicability of this technology. Here, we demonstrate that interleukin-18 (IL-18)-secreting CAR T cells exhibit enhanced in vivo expansion and persistence and significantly increase long-term survival in syngeneic mouse models of both hematological and solid malignancies. In addition, we demonstrate that IL-18-secreting CAR T cells are capable of modulating the tumor microenvironment, as well as enhancing an effective endogenous anti-tumor immune response. IL-18-secreting CAR T cells represent a promising strategy to enhance the clinical outcomes of adoptive T cell therapy. [Display omitted] •IL-18-secreting CAR T cells enhance anti-tumor efficacy via IL-18 autocrine stimulation•IL-18-secreting CAR T cells favorably alter EL4 tumor microenvironment•IL-18-secreting CAR T cells enhance the anti-tumor response of endogenous T cells•IL-18-secreting CAR T cells are efficacious in syngeneic models without preconditioning Avanzi et al. generate CAR T cells that secrete IL-18 and show improved activity in syngeneic hematologic and solid tumor models without prior preconditioning. They further show enhanced recruitment and anti-tumor activity of endogenous T cells.